White-nosed coati Nasua narica (Carnivora: Procyonidae) as a potential poUinator of Ochroma pyramidale (Bombacaceae) - Mora, José M (1999)
Biotic pollination predominates in tropical forests (Hartshorn 1983). Although bats play an important role as pollinators, it has been suggested that no plant species depends entirely on eutherophily (Vaughan 1986).